Tanggung Jawab Pengelola Area Parkir Atas Kehilangan Kendaraan Bermotor di Area Parkir - Kencana, Annisa Puspa; Arifinal, Mochamad; Efriyanto, Efriyanto (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2024)
Safekeeping of goods is an agreement activity "real” which is regulated in the Civil Code. In carrying out parking activities, every asset owned by the Regional Government in Cilegon City is regulated by the Transportation Service.In parking activities, there is a legal relationship between the parking manager and the parking consumer, so if a motor vehicle is lost, the parking manager must be responsible for the lost item. The identification of this research problem is, what is the responsibility of the Cilegon City Transportation Service Parking UPT for the loss of motorized vehicles in the Cilegon City Regional Hospital parking area and how compensation is determined by the Cilegon City Transportation Service Parking UPT as the parking manager for the loss of motorized vehicles at the Cilegon City Regional Hospital. The theories used in this research are responsibility theory and legal protection theory. The method used in preparing this thesis is the normative juridical method. use statutory regulations and legal principles in conducting research. The data sources used in this research are primary and secondary data sources which were analyzed qualitatively. The research results from this thesis are a form of legal responsibility of the Cilegon City Transportation Department Parking UPT as the parking manager to be able to provide compensation in accordance with the Civil Code and Jurisprudence as well as legal protection for determining the nominal compensation that parking consumers must receive for losses. motor vehicle. The conclusion of this thesis research is that the responsibility of the Cilegon City Transportation Service Parking UPT for lost motor vehicles in the Cilegon City Regional Hospital parking area has not been carried out as it should. The Transportation Service Parking UPT does not keep its promise to be responsible at the agreed time. And the determination of compensation by the Cilegon City Transportation Service Parking UPT as management in the transportation service parkirng UPT as management in the transportation sector, especially parking is not carried out based on legal or economic procedures.